Comprehensive Review of Metastatic Breast Carcinoma in Cytology Specimens - Swikrity U. Baskota; Daniel Qazi; Ashish Chandra; Poonam Vohra (MDPI AG, 2022)
Breast carcinomas are known to metastasize to various organs of the human body. Fine needle aspiration cytology or exfoliative cytology often are the standard method for diagnosis at these metastatic sites due to ease of procurement of diagnostic material, accessibility, less complications, high sensitivity, and specificity of diagnosis and evaluation of biomarker status needed to guide future management. This comprehensive review article discusses in detail metastatic patterns, cytomorphology of metastatic breast cancer at different body sites, immunohistochemistry needed for diagnosis of breast carcinoma, sensitivity and specificity of diagnosis and breast biomarker assays in the cytology material.